PENGARUH PERPUTARAN KARYAWAN, PERILAKU DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK SUMSEL BABEL PALEMBANG - Puspita, Santi (Universitas muhammadiyah palembang, 2012)
The purpose of this research is to know the influence of leadership, turn over and attitude for employee satisfaction of PT. Sumsel Babel Bank Palembang not only jointly but also partially which used cluster sampling of 76 employees of Sumsel Babel Bank Palembang employees. Samples which used determined from Slovin formula that have 76 employees. Data collected from the answer of respondent questionnaire that explain about variable research which have weights between 1-5 Likert scale. Descriptive data analysis done after the data is converted to a form of interval using the Successive Interval. multiple linier regression analysis which is helped by SPSS Program for Windows version 16 to test the research hypothesis T test analysis results proved that leadership, turn over of employee, the attitude of employee have real influence for employee satisfaction of Sumsel Babel Palembang Bank which the constanta is 0,866. Leadership variable have real influence which regression coefficient is 0,40. Turn over of employee variable which regression coefficient is 0,162 and attitude of employee is bigger than F-table (? 0,05 = 2,372). It means that if the error rate 0,05, it will influence for leadership, turn over of employee, and attitude of employee for employee satisfaction of Sumsel Babel Palembang Bank.